Effects of Clitoria Ternatea on renal ischemia and reperfusion injury in rats - Şule Melek; Ahmet Uyar; Hürrem Turan Akkoyun; Serdar Altun; Mahire Bayramoğlu Akkoyun; Fatma Karagözoğlu; Suat Ekin; Aydın Şükrü Bengü; Gültekin Atalan; Ahmet Bakir (Revista Científica, 2025)
Ischemia-reperfusion (I/R) injury refers  to  damage  caused by the temporary interruption of blood flow into an organ/ tissue and the restoration of circulation. This injury, which affects many vital organs, is still an important clinical and surgical problem. This study aims to investigate the effect of antioxidant and anti-inflammatory effects of Clitoria ternatea on renal I/R injury in rats. Twenty-four male Wistar albino rats were clustered into 4 groups, 6 rats in each (Control, I/R group, Clitoria ternatea group, I/R group + Clitoria ternatea group). At the end of the experimental procedures, all groups were euthanised in accordance with ethical rules. Blood and tissue samples were taken and subsequent biochemical (MDA, SOD, CAT, GSH-Px, BUN, Na, K, creatine), histopathological and immunohistochemical analyses demonstrated that Clitoria ternatea effectively prevented I/R-induced renal injury in rats. Based on these findings, Clitoria ternatea may be considered a potential therapeutic agent for the prevenstion of I/R-induced kidney damage.